Financial Reporting Quality and Information Asymmetry: A Review of Empirical Literature - Ayagi , Sunusi Ridwan; Salisu, Muhammad (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2023)
This paper reviewed empirical works conducted and published from 2008 to 2013 regarding impact of financial reporting quality on information asymmetry as implied by signaling theory. An integrative/critical review approach was used. Findings of the paper are that despite being mixed and varied, the results obtained by most of the studies carried out are in agreement with signaling argument, that is, sending high quality financial information (FRQ) trims down the level of information asymmetry between corporate firms and financial statements users. Also, in line with the summary of major findings, the paper concluded that signaling theory best explain the relationship between FRQ and IA and thus, engaging in FRQ will substantially reduce asymmetric information in capital markets and other economic dealings involving corporate firms and financial statements users. Based on the conclusions drawn, the paper suggested that corporate firms should be engaging in timely reporting of relevant information to users of their financial statements.